An unyielding challenge for refractory hyponatremia in neuroendocrine cervix carcinoma: a case report - Li, Minzhen; Yin, Rutie; Zhong, Lan; Song, Liang (Frontiers in Endocrinology, 2025)
Neuroendocrine neoplasms (NENs) originate from peptidergic neurons and neuroendocrine cells, possessing endocrine functions, and are commonly found in the gastrointestinal tract, pancreas, and lungs. Neuroendocrine cervix carcinoma (NECC) is infrequent, prone to early dissemination and distant metastasis, and generally has a poor prognosis. The presence of electrolyte imbalance in such cases is even rarer. Here, we present a case of advanced NECC patient who developed refractory hyponatremia, accompanied by severe clinical symptoms such as palpitations, chest tightness, hematemesis, and delirium. Despite extensive investigations, all efforts to elucidate the underlying causes of hyponatremia were negative, suggesting a multifactorial etiology. Next-generation sequencing was also employed to explore the underlying mechanisms at the genetic level. Managing this case posed significant challenges for gynecologic oncologists, as the patient showed minimal response to various treatments, including sodium supplementation, fluid restriction or replenishment, chemotherapy modification, and the use of vasopressin-2 receptor antagonist. This case underscores the importance of monitoring and managing electrolytes in patients with gynecologic NENs, even though the exact mechanisms of such imbalances may remain elusive.